Foreign trade prices in the Council for Mutual Economic Assistance - Hewett, Edward A. (Cambridge : University Press, 1974)
This book examines CMEA foreign trade, prices and other related issues
Original version of this study submitted as the author's thesis, University of Michigan.
Includes bibliographical references.
mf 24/01/2019
Loans
Keywords: Price regulation; Pricing; Europe, Eastern